2022
DOI: 10.2196/38206
|View full text |Cite
|
Sign up to set email alerts
|

Automated Digital Interventions and Smoking Cessation: Systematic Review and Meta-analysis Relating Efficiency to a Psychological Theory of Intervention Perspective

Abstract: Background Smoking remains a highly significant preventable global public health problem. In this context, digital interventions offer great advantages in terms of a lack of biological side effects, possibility of automatic delivery, and consequent human resource savings relative to traditional interventions. Such interventions have been studied in randomized controlled trials (RCTs) but have not been systematically reviewed with the inclusion of text-based and multiplatform-based interventions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…of studies Population Digital intervention Control Countries/regions No. of studies in WPR a Combined effects b 1 Smoking cessation Sha L, 2022 9 19 High risk (smoker) Short messaging service Mobile Apps None Self-help guideline Asia (nWPR) (n = 2) Europe (n = 7) South America (n = 1) North America (n = 5) WPR (n = 3) Multi-center (the US, UK, Australia, and Singapore) (n = 1) Australia (n = 1) China (n = 2) New Zealand (n = 1) Singapore (n = 1) Benefits for smoking cessation, pooled RR = 1.6 (95% CI: 1.3, 1.9) 2 Smoking cessation Kock L, 2019 10 42 High risk (smoker) Short messaging service Mobile Apps Usual care Mixed Asia (nWPR) (n = 1) Europe (n = 8) North America (n = 30) WPR (n = 3) Australia (n = 2) China (n = 1) Benefits for smoking cessation, pooled RR = 1.6 (95% CI: 1.4, 1.8) 3 Smoking cessation Whittaker R, 2019 11 26 High risk (smoker) Short messaging service Mobile Apps None Self-help guideline Europe (n = 7) North America (n = 9) WPR (n = 9) Multi-center (the US, UK, Australia, and Singapore) (n = 1) Australia (n = 4) China (n = 4) New Zealand (n = 2) Singapore (n = 1) Benefits for smoking cessation, pooled RR = 1·5 (95% CI: 1.2, 2.0) 4 Healthy diet Beck Silva KB, 2022 12 13 General Internet-based services Usual care Asia (nWPR) (n = 1) Europe (n = 5) North America (n = 7) NA Benefits for reducing consumption of fats, pooled SMD = −0.1 (95% CI: −0.2, −0.1) 5 Healthy diet, Exercise, Weight loss Robert C, 2021 1...…”
Section: Applications Of Dhealth Approaches In Cmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…of studies Population Digital intervention Control Countries/regions No. of studies in WPR a Combined effects b 1 Smoking cessation Sha L, 2022 9 19 High risk (smoker) Short messaging service Mobile Apps None Self-help guideline Asia (nWPR) (n = 2) Europe (n = 7) South America (n = 1) North America (n = 5) WPR (n = 3) Multi-center (the US, UK, Australia, and Singapore) (n = 1) Australia (n = 1) China (n = 2) New Zealand (n = 1) Singapore (n = 1) Benefits for smoking cessation, pooled RR = 1.6 (95% CI: 1.3, 1.9) 2 Smoking cessation Kock L, 2019 10 42 High risk (smoker) Short messaging service Mobile Apps Usual care Mixed Asia (nWPR) (n = 1) Europe (n = 8) North America (n = 30) WPR (n = 3) Australia (n = 2) China (n = 1) Benefits for smoking cessation, pooled RR = 1.6 (95% CI: 1.4, 1.8) 3 Smoking cessation Whittaker R, 2019 11 26 High risk (smoker) Short messaging service Mobile Apps None Self-help guideline Europe (n = 7) North America (n = 9) WPR (n = 9) Multi-center (the US, UK, Australia, and Singapore) (n = 1) Australia (n = 4) China (n = 4) New Zealand (n = 2) Singapore (n = 1) Benefits for smoking cessation, pooled RR = 1·5 (95% CI: 1.2, 2.0) 4 Healthy diet Beck Silva KB, 2022 12 13 General Internet-based services Usual care Asia (nWPR) (n = 1) Europe (n = 5) North America (n = 7) NA Benefits for reducing consumption of fats, pooled SMD = −0.1 (95% CI: −0.2, −0.1) 5 Healthy diet, Exercise, Weight loss Robert C, 2021 1...…”
Section: Applications Of Dhealth Approaches In Cmdsmentioning
confidence: 99%
“…Various ICTs were used for daily tasks and schedule management in behavior intervention. 9 , 10 , 11 , 13 , 17 Wearable devices and/or videoconferencing for exercise, and mobile apps used for recording diet, were also effective for behavior interventions. 15 , 16 , 18 …”
Section: Applications Of Dhealth Approaches In Cmdsmentioning
confidence: 99%
“…After 3 months, e-visit participants, when compared with usual treatment participants, were 4.13 (95% CI 1.06-16.10; P =.04) times more likely to have reduced their number of cigarettes smoked per day by at least 50%. In a recent systematic review that evaluated the efficacy of digital interventions in randomized clinical trial studies of smoking cessation, 19 trials (15,472 participants) were included in the analysis, and the overall abstinence rate (percentage of participants who did not smoke during a follow-up period of at least 3 months) at the end point was 17.8% (95% CI 17%-18.7%); the authors concluded that digital health had a clear positive effect when compared to self-help guidelines or no intervention [ 35 ].…”
Section: Evidence Of Mhealth Focused On Smoking Cessationmentioning
confidence: 99%
“…It is therefore clear that it is necessary to carry out interventions that do not imply the need for pharmacological treatment and to have data on efficacy and efficiency that support their generalization to the smoking population. Other reviews that address this topic have been performed [ 33 - 35 ]. However, this viewpoint paper is not so much a review in itself, but rather an update on the state of digital health in general and its impact on smoking cessation programs.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account this small body of research, novel scientific knowledge would be gained from examining the question of whether pharmacotherapy improves the efficacy of existing digital interventions shown efficacious for smoking cessation. Given that digital interventions are becoming the most common self-help intervention for smoking [3,30,31], understanding whether or not medications improve the efficacy of smoking cessation apps is a timely question.…”
Section: Introductionmentioning
confidence: 99%